1993
DOI: 10.1111/j.1467-1770.1993.tb00627.x
|View full text |Cite
|
Sign up to set email alerts
|

Psycholinguistic Determinants of Foreign Language Vocabulary Learning

Abstract: This paper reviews the psycholinguistic factors that affect ease of learning of foreign language (FL) vocabulary and investigates their role in 47 students' learning of German under Repetition, Keyword or “Own” strategy conditions. Native‐to‐foreign learning is shown to be easier the more the FL words conform to the phonological (0.40 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
266
3
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(289 citation statements)
references
References 74 publications
18
266
3
2
Order By: Relevance
“…Several factors have been identified to impact the learnability of FL vocabulary including words' grammatical properties, such as POS (Ellis & Beaton, 1993;Nation, 2001;Schmitt, 2010). It has been reported by, among others, Laufer (1997) and Milton (2009), that nouns are easier to learn than verbs, which in turn are easier to learn than adjectives.…”
Section: Parts Of Speechmentioning
confidence: 99%
“…Several factors have been identified to impact the learnability of FL vocabulary including words' grammatical properties, such as POS (Ellis & Beaton, 1993;Nation, 2001;Schmitt, 2010). It has been reported by, among others, Laufer (1997) and Milton (2009), that nouns are easier to learn than verbs, which in turn are easier to learn than adjectives.…”
Section: Parts Of Speechmentioning
confidence: 99%
“…During the test, which measured productive L2 vocabulary knowledge, either the pictures or the L1 translations constituted the cues for recall of the L2 words. The results showed that the translation learning condition resulted in better recall performance than the picture condition and cognates and high-frequency words were easier to learn than noncognates and low-frequency words (see also N. Ellis & Beaton, 1993). Kroll, Michael and Sankaranarayanan (1998) investigated L2 vocabulary learning under conditions differing in the allowance of L1 word mediation and concept mediation.…”
Section: Psycholinguistic Studiesmentioning
confidence: 99%
“…For example, an English person learning the German word Raupe (meaning caterpillar) could use the English word rope (similar in sound to Raupe) as a keyword, while constructing a mental image of a caterpillar stretched out in more than its fullest length (exaggeration helps) on a rope. Research in this area has been reviewed by Cohen (1987), N. Ellis and Beaton (1993), Hulstijn (1997a), and Rodríguez and Sadoski (2000). Cohen (1987) concludes his review with the claim that memory techniques have been shown to produce high retention rates but are not intended to replace other, more natural, approaches to vocabulary learning.…”
Section: Practice-based Educational Studiesmentioning
confidence: 99%
“…Her theory is compatible with the noticing hypothesis, which when applied to vocabulary learning, suggests memory traces of words are created through interactive learning activities that promote the noticing of particular words (Robinson, 1995). The imageability of words, the degree to which words can elicit mental images, also affects the learning of new vocabulary since the greater the imageability of a word, the greater the chance of it being recalled (Ellis & Beaton, 1993;Paivio, 1971). Student creation of multimedia materials to acquire new vocabulary involves them in active learning where they focus on particular words, make lexical associations, and find images to help them remember the meaning of words.…”
Section: Psycholinguistic Theories Of Active Vocabulary Learningmentioning
confidence: 70%